Adoption of Web 2,0 by Academic Libraries in Nigeria (2015)
This study is an attempt to ascertain the extent to which academic libraries in Nigeria have adopted web 2.0 for library services. The researchers surveyed these libraries by visiting their websites and social media pages to determine the level of adoption and implementation of web 2.0 tools. The libraries were classified into 3 groups and the adoption of web 2.0 was tested across the groups using Analysis of Variance. Other data gathered were analyzed and presented using tables. The analysis indicates that the adoption of the web 2.0 tools in information services is still at the budding stage. Only a few of the libraries have a proper structure for the coordination and integration of these tools in the delivery of information services. A significant proportion of those in this category are private university libraries. The implementation of web 2.0 tools on the websites of the federal and state universities is not as advanced like those of their counterparts in the private universities. Beyond the hype, it is important for academic libraries to implement the emerging technology to maximize its benefits for teaching, learning and research, and also to promote the relevance of libraries in the changing information terrain.